Pengaruh Volume Alir Udara terhadap Pola Sebaran Gelembung pada Bubble Plume - Trihutomo, Prihanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
Bubble plume is the effective way to generate bubbles by air injection from the bottom of bath. Bubble plumes is important for gas transfer process, turbulence generation, collecting the surface-floating substance, and also important to mixing effect in chemical process. This research aims to analyse effect of gas flowrate on bubble dispersion pattern in bubble plume. An experimental apparatus to investigating bubble dispersion consists of a transparent vertical bath is 500 mm length, 24 mm wide and 750 mm height. The bubble generator consists of 110 needles, each needle is 0.25 mm in diameter, installed at the bottom of bath. The experimental method was used in this research. Data were taken by high resolution digital camera. Bubble dispersion pattern was generated by air injection from the bottom of bath. The experiments was done at various gas flowrate that is 4.16 x 10-6m3/s, 6.67 x 10-6m3/s,Â 10.4 x 10-6m3/s, 18.83 x 10-6m3/s dan 31.6 x 10-6m3/det. Data analyse using ImageJ software to get number, dimension and position of bubble. The experimental results show that increase of gas flowrate causes the number and the diameter of bubble increase and also to widen of diameter interval and bubble dispersion. In each of gas flowrate the bubble trend coalescence intermittently. The intermittent coalescence decrease with the increase of gas flowrate.